Heir for his empire - Green, Abby (Harlequin presents, 2024)
The heir he didn't plan for is her best kept secret. USA TODAY bestselling author Abby Green captivates with this shock baby romance. Returning for her... Staying to secure his heir. CEO Ajax Nikolau rules his empire with legendary control, until two sizzling nights with lawyer Erin Murphy threatens it all. Because a year later, he discovers the bombshell that could destroy every wall he's built--he's a father! And he will protect what's his... Abandoned as a child, Erin vowed to always rely on herself. But when the paparazzi discover the new Nikolau heir, they're forced into hiding. Isolated together on a Greek island, forgetting their passionate connection becomes impossible. Especially when Erin uncovers why Ajax is so determined to claim what's his...